'Til faith do us part: how interfaith marriage is transforming America - Riley, Naomi Schaefer (Oxford University Press, 2013)
Defining holy matrimony -- The road to marriage -- The vows we make -- Passing it on -- The December dilemma -- Interfaith divorce -- Muslims in the melting pot -- The welcome mat -- Jews, Mormons, and the future of interfaith marriage